2022
DOI: 10.1186/s13018-022-03160-y
|View full text |Cite
|
Sign up to set email alerts
|

Safety of surgical hip dislocation in femoral head fracture and dislocation (FHFD) and avascular necrosis risk factor analysis of FHFD: midterm results confirmed by SPECT/CT and MRI

Abstract: Background The study aim was to report the treatment outcomes of trochanteric flip osteotomy (TFO) with surgical hip dislocation (SHD) for femoral head fracture and dislocation (FHFD) and to investigate the risk factors for avascular necrosis (AVN) of the femoral head. Methods The data of 34 patients (29 men, 5 women; mean age 37.9 years) diagnosed with FHFD and treated with TFO with SHD between May 2009 and February 2018 with an average follow-up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Yoon, YC et al (2022) 11 showed TFO with SHD is a safe and useful approach for the treatment of FHFD. Particular attention should be paid when treating femoral head fractures associated with displaced femoral neck fractures because of the high risk of AVN development.…”
Section: Resultsmentioning
confidence: 99%
“…Yoon, YC et al (2022) 11 showed TFO with SHD is a safe and useful approach for the treatment of FHFD. Particular attention should be paid when treating femoral head fractures associated with displaced femoral neck fractures because of the high risk of AVN development.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, in clinical practice, there is no routine examination to assess the blood flow of the femoral head after a Pipkin fracture, except for MRI, for the diagnosis of AVN. Recent studies have quantified the blood flow and perfusion status of the femoral head after hip fracture using single-photon emission computed tomography (SPECT) with computed tomography (CT) to evaluate the blood flow status in the bone while precisely localizing the necrotic site [ 47 49 ]. We recommend initiating the trend to judge the blood flow status with axillary examination with SPECT or PET-CT to predict osteonecrosis of the femoral head even after implant insertion after surgical or non-surgical management of Pipkin fractures.…”
Section: Discussionmentioning
confidence: 99%
“…During the examination of avascular necrosis of the femoral head by MRI, high resolution of soft tissue can be produced, and bone marrow edema, necrosis and granulation infiltration can be clearly displayed. [ 28 , 29 ] According to the relevant meta-analysis, the diagnosis rate of avascular necrosis of the femoral head by MRI was higher than that by X-ray and CT. [ 30 ]…”
Section: Iconographymentioning
confidence: 99%